Conversational Implicature in Trevor Noah’s Stand-Up Comedy Show Performance at the 2022 White House Correspondents’ Dinner and Lesson Plan - Nurrohmah, Annisa; Suyatman, Ujang; Listiani, Toneng (Raja Zulkarnain Education Foundation, 2025)
This study aims to discuss and describe two aspects: 1) conversational implicature and maxim violations in Trevor Noah's stand-up comedy, and 2) the lesson plan of conversational implicature and maxim violations in Trevor Noah's stand-up comedy using a constructivist approach through Google Forms. A descriptive, qualitative approach based on Grice's implicature theory was employed in this study to analyze 17 of Noah's utterances taken from a YouTube video entitled